Enhancement of Health‐Promoting Properties While Substituting Exogenous Citric Acid by Seabuckthorn (Hippophae salicifolia) Pulp in Preparation of Sweet Orange (Citrus sinensis) Ready‐to‐Serve Beverage. Issue 4 (17th May 2013) - Sharma, Satish Kumar; Yadav, Vijay Kumar; Rao, Virendra Kumar; Dixit, Anil Kumar
Abstract To optimize the blend of sweet orange cv. Malta Common (SOM) and Seabuckthorn (SBT) pulps, for preparation of SOM‐based Ready‐to‐serve (RTS) beverage rich in health‐enhancing functional bioactives, a design layout with variable levels of three factors i.e., SBT pulp (13.18–46.82%) in SOM–SBT mixed pulp, sugar (109.77–160.23% of mixed pulp used) and peel oil (0.127–1.47 mL/L of beverage), were studied. The product with 40% SBT pulp in SOM–SBT mixed pulp, 140% sugar and 0.40 mL/L of peel oil was optimized with an overall desirability of 0.81. Optimized product had total soluble solids14.26 brix and acidity 0.34%, with vitamin C, amino acid, and total phenols at 21.75, 22.59 and 39.10 mg%, respectively, besides having high sensory acceptability. Thus, SBT pulp can substitute the requirement of exogenous addition of citric acid in preparation of SOM based RTS beverage besides enriching the product in its health enhancing attributes. Practical Applications With the increasing preference of consumers for natural and natural like ingredients in various food products, the technology of blending various juices to get desired combination of nutrients and quality characteristics, offers a great promise for the fruit juice industry. By this technique, a particular juice deficient in a particular nutrient can be enriched by blending with another natural juice, extract, etc., for compensating the deficit, without much compromising with the basic nutrient composition and consumer acceptability of the original juice. The results of the study therefore, can be utilized directly for practically, manufacturing blended juices from Seabuckthorn and orange fruits.